What is the relationship between sales growth and insolvency risk? - Nataša Šarlija; Sanja Šimić; Biljana anković (Naše gospodarstvo / Our Economy, 2023)
Sales growth is essential for an enterprise's survival and financial growth.If an enterprise manages to achieve sales growth, its expansion can be accomplished. However, does sales growth always have only positive effects?If the enterprise is not collecting enough cash, it can miss a payment on its debt, triggering a series of events that can lead to its insolvency. The goal of the paper is to explore the relationship between an enterprise's sales growth and its insolvency. The relationship is tested empirically on the dataset of 4271 SMEs in Croatia. The results confirmed that there is a relationship between sales growth and insolvency. Better indicators exist with solvent andgrowing SMEs than with insolvent and non-growing. Results have also shown that high growth can be at the same time a high risk. The paper contributesto a deeper understanding of the relationship between sales growth and insolvency and empirically demonstrates that sales growth over 200% peryear induces the highest probability of insolvency compared to other lowerlevels of growth.
Keywords: G30; G32; M21; 330; SMEs growth; Insolvency risk; Sales growth; Financial indicators; Insolvency prevention; Bankruptcy